Effects of acute cool water immersion on time trial performance and exercised- induced oxidative stress among endurance cyclists in the heat - Lit, K.-W.; Chen, C.-K.; Ang, B.-S. (Journal of Athletic Enhancement, 2014)
Background: Cold water immersion has been used as a modality for recovery among elite athletes. This study investigated the effects of acute cool water immersion (CWI) at 25°C following prolonged submaximal cycling on time trial (TT) performance and oxidative stress. Methods: Nine trained male cyclists performed a randomized crossover trial comprising of 60 minutes of cycling at 70% VO2max, followed by 30 minutes of CWI and subsequently a 20 km cycling time trial. Environmental conditions were maintained at 31.2 ± 0.3 °C and relative humidity of 72.0 ± 0.7%. Results: Prior to the 20 km TT, rectal temperature (Trec) of the participants in the CWI trial was significantly (p<0.05) lower than the air cooling (AC) trial (36.1 ± 0.3°C vs 37.1 ± 0.3°C respectively). Similarly, resting heart rate of the participants in the CWI trial following CWI was significantly (p<0.05) lower than the AC trial (61.9 ± 10.0 beats.min-1 vs 89.9 ± 8.3 beats.min-1). Average cycling speed in the CWI trial was significantly (p<0.05) faster than the AC trial (27.4 ± 2.1 km.h-1 vs 25.9 ± 2.4 km.h-1). Time to complete the 20km TT in the CWI trial was significantly (p<0.05) shorter than the AC trial (43.8 ± 3.3 min vs 46.4 min ± 4.5 min respectively). During the TT, Trec in the CWI trial was significantly (p<0.05) lower than the AC trial (37.8 ± 0.4°C vs 38.5 ± 0.7°C respectively). However, there were no significant differences in serum F2-Isoprostanes and GSH/ GSSG ratio during both trials. Conclusion: CWI at 25°C lowers core body temperature effectively and improves TT performance of endurance cyclists in a hot and humid condition compared to normal air cooling.